Mosquito Shield-Transfluthrin Spatial Repellents Against Malaria-Transmitting Anopheles: A Systematic Review and Meta-Analysis - Dinda Nurhanifah; Dian Dewi; Anggie Azzura; Hanum Fadhilah; Fitrawan Alfiansyah; Anastasia Renate; Prihati Pujowaskito (The ASEAN Journal of Military and Preventive Medicine, 2025)
Background: Malaria remains a major mosquito-borne disease in tropical and subtropical regions. Although insecticide-treated nets and indoor residual spraying have contributed to malaria control, residual transmission and pyrethroid resistance require complementary vector control strategies. Mosquito Shield™ is a transfluthrin-based passive spatial repellent designed to reduce human–Anopheles contact. This systematic review and meta-analysis aimed to evaluate the effectiveness of Mosquito Shield in reducing exposure to malaria-transmitting Anopheles mosquitoes. Methods: A systematic literature search was conducted in November 2024 using Medline/PubMed, Scopus, ScienceDirect, and Cochrane for studies published between 2019 and 2024. Eligible studies were randomized or cluster-randomized controlled trials conducted in malaria-endemic or epidemic-prone areas that evaluated transfluthrin-based Mosquito Shield compared with placebo. Outcomes included Human Landing Catch, incidence rate ratio or risk ratio, and protective efficacy. Risk of bias was assessed using RoB 2.0, and meta-analysis was performed using Review Manager 5.4.1 with a random-effects model. Discussion: Two studies met the inclusion criteria. Mosquito Shield reduced Anopheles landing rates compared with placebo, with protective efficacy ranging from 34.2% to 70%. The pooled risk ratio was 0.45 (95% CI: 0.21–0.98; p = 0.04), indicating a significant reduction in mosquito exposure. However, heterogeneity was high (I² = 95%). Conclusion: Mosquito Shield™ may reduce exposure to malaria-transmitting Anopheles mosquitoes, but evidence remains limited by the small number of studies and substantial heterogeneity.